1996
DOI: 10.2307/2389946
|View full text |Cite
|
Sign up to set email alerts
|

Below-Ground Microbial and Microfaunal Responses to Artemisia tridentata Grown Under Elevated Atmospheric Co 2

Abstract: JSTOR is a not-for-profit service that helps scholars, researchers, and students discover, use, and build upon a wide range of content in a trusted digital archive. We use information technology and tools to increase productivity and facilitate new forms of scholarship. For more information about JSTOR, please contact support@jstor.org. Summary 1. Soil microbes are fed primarily by root-derived substrates, fulfil functions such as mineralization, immobilization, decomposition, pathogeneity and improvement of p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
75
1

Year Published

1998
1998
2020
2020

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 142 publications
(80 citation statements)
references
References 21 publications
4
75
1
Order By: Relevance
“…The greater percentage of root length colonized in P. lanceolata under C ELEV contrasts with the situation reported not only for T. repens by Jongen et al (1996) but also for other C $ plants : Gossypium , Pascopyrum (Monz et al, 1994), Artemisia (Klironomos et al, 1996) and Liriodendron (O'Neill et al, 1991). Sequential harvests in the latter study revealed progressive increases in total root length with time without change in the proportion of colonized to non-colonized root.…”
Section: contrasting
confidence: 79%
See 4 more Smart Citations
“…The greater percentage of root length colonized in P. lanceolata under C ELEV contrasts with the situation reported not only for T. repens by Jongen et al (1996) but also for other C $ plants : Gossypium , Pascopyrum (Monz et al, 1994), Artemisia (Klironomos et al, 1996) and Liriodendron (O'Neill et al, 1991). Sequential harvests in the latter study revealed progressive increases in total root length with time without change in the proportion of colonized to non-colonized root.…”
Section: contrasting
confidence: 79%
“…In the case of the last species, however, although the proportions of root length colonized did not change, the total mycorrhizal root length almost doubled. Klironomos, Rillig & Allen (1996) found that significantly more root length was occupied by arbuscular hyphae and arbuscules at elevated CO # , but only under conditions of low nutrient supply.…”
Section: Atmospheric Comentioning
confidence: 90%
See 3 more Smart Citations